Formulasi Pertanggungjawaban Pidana Korporasi Dengan Adanya Peraturan Mahkamah Agung No. 13 Tahun 2016 - Michelle Kristina (JURNAL YUSTIKA: MEDIA HUKUM DAN KEADILAN, 2018)
The development of the concept of corporation not only had a positive impact but also followed by the development of crimes that could be done using corporations or also called corporate crime. Many laws and regulations that have accommodated corporation as legal subjects that can be asked for corporate criminal responsibility have not been followed by regulations governing procedures or procedures for examining corporations as perpetrators of criminal acts. This is very necessary because of the differences in characteristics between corporate crime and other conventional crimes. Responding to legal requirements that have been very urgent and there are distinct challenges for law enforcers because of the different treatment, then the Supreme Court issues Supreme Court Rules No. 13 of 2016. The problem regarding the procedure for corporate sentencing involved in criminal offenses is not only talking about material law but also about formal law or its procedural law. One of the aims and objectives of its formation is to fill the vacuum of criminal procedural law which until now has not regulated the procedures for handling corporations that carry out criminal cases. Supreme Court Rules No. 13 of 2016 is a legal rule aimed at assisting law enforcement officials in handling criminal cases with corporate actors and/or their administrators. This then became one form of thinking that could be the basis for assisting in the formation of criminal procedural laws governing corporations.